Determinan Perilaku Seks Pranikah Remaja Berdasarkan Teori Health Belief Model (HBM) - Laila Hidayah Santoso; Muji Sulistyowati (Universitas Airlangga, 2024)
Background: Premarital sexual behavior refers to sexual activities conducted without the formal process of marriage, as recognized by law, religion, or belief systems. Premarital sexual behavior has become a phenomenon and a growing issue commonly encountered in society. Such behavior is feared to contribute to sexually transmitted diseases, and unwanted pregnancies, and may encourage child marriage practices. The Health Belief Model can predict individuals in making health-related decisions, including the prevention of premarital sexual behavior. Objectives: This study aims to analyze the determinants of premarital sexual behavior among adolescents based on the Health Belief Model. Methods: This study was descriptive quantitative research using a cross-sectional design. The sample used was 90 respondents from 10th and 11th grade students, who were randomly selected using proportional random sampling within a one-month period. Data collection with questionnaires related to premarital sexual behaviour based on Health Belief Model components in high schools in Gresik Regency. This study uses SPSS analysis with the chi-square test. Result: The results showed that 4.4% of respondents engaged in premarital sexual behavior. The perceived severity value was p=0.005, perceived barriers value was p=0.006, perceived susceptibility (p=1.000), perceived benefits (p=1.000), perceived self-efficacy (p=0.050), and cues to action (p=1.000). Conclusions: The study concludes that is a significant relationship between perceived severity and perceived barriers to premarital sexual behavior among adolescents. However, perceived susceptibility, perceived benefits, perceived self-efficacy, and cues to action do not have a significant relationship with premarital sexual behavior among adolescents. It is suggested that adolescents enhance their understanding of premarital sexual behavior by seeking accurate and reliable information, and by choosing friends and social environments wisely to avoid negative influences or the desire to engage in premarital sexual behavior.